1999
DOI: 10.1046/j.1365-2044.1999.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of steam sterilisation at 134 °C on light intensity provided by fibrelight Macintosh laryngoscopes

Abstract: SummaryWe studied the repeated effect of sterilisation on light intensity in laryngoscopes from Penlon, Riester, Heine (two different blades), Medicon and Upsher. Light intensity was measured by a light meter using two methods. Measurements were performed before the decontamination procedure was carried out and subsequently after each series of 25 procedures until a total of 200 cycles was reached. Using method 1 (and 2), the reduction in light intensity after 200 cycles was 100% (100%; no light emitted), 37% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 9 publications
3
19
1
Order By: Relevance
“…In a previous study it was shown that there were substantial differences between fibrelight laryngoscope blades' ability to withstand the detrimental effects of steam sterilisation at 134°C [7]. In addition, even the best performing blades showed considerable reductions in light intensity after only 200 cycles [7]. However, this study had several limitations such as the small number of participating manufacturers, testing of only one blade of each type, and steam sterilisation of all blades at 134°C.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…In a previous study it was shown that there were substantial differences between fibrelight laryngoscope blades' ability to withstand the detrimental effects of steam sterilisation at 134°C [7]. In addition, even the best performing blades showed considerable reductions in light intensity after only 200 cycles [7]. However, this study had several limitations such as the small number of participating manufacturers, testing of only one blade of each type, and steam sterilisation of all blades at 134°C.…”
mentioning
confidence: 90%
“…Recently, Control of Substances Hazardous to Health (COSHH) regulations applicable throughout the European Union have rendered many high-level disinfectants no longer easily accessible. This has resulted in an increased need to rely on thermal disinfection and ⁄ or sterilisation procedures, which are known to be detrimental to fibrelight bundles [7]. In a previous study it was shown that there were substantial differences between fibrelight laryngoscope blades' ability to withstand the detrimental effects of steam sterilisation at 134°C [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We would advise others to carefully assess the options in their hospital, such as using condoms to cover the blade [12], disposable blades or even changing to sterilizing used laryngoscopes. It is interesting to note that even changing the method of cleaning laryngoscopes may change their performance [8].…”
Section: Discussionmentioning
confidence: 99%
“…We measured illumination by a method similar to that previously described [8] (Fig. 1), lining the blade up with a mark on the inside wall.…”
Section: Methodsmentioning
confidence: 99%